The convenience store by the sea - Machida, Sonoko, 1980- (G.P. Putnam's Sons, an imprint of Penguin Random House, LLC, 2025)
"Welcome to Tenderness! A quaint seaside town in Kitakyushu, Mojiko is full of hidden delights. And one unexpected treasure is the 24/7 convenience store, Tenderness. Sure, it's a bit odd that the incredibly handsome manager has his own fan club. And perhaps the customers are somewhat eccentric, if not entertaining. But there's a warmth about the store that draws you in. The truth is, Tenderness is different. Operating only in Kyushu, Tenderness stands firm and proud by its motto "Caring for People, Caring for You", no matter the cause. And for Mitsuhiko, dishing out delicious food is simply the appetizer to his unsolicited but hearty wisdom on the town's shenanigans. An international bestseller with over half a million copies sold between Japan and South Korea, The Convenience Store by The Sea tells the delightfully quirky and heartfelt stories of the store's customers and employees, offering us all a unique recipe for a good, fulfilling life"-- Provided by publisher.